PENINGKATAN KUALITAS PENDIDIKAN MELALUI PENGEMBANGAN HARD SKILLS PENDIDIK: STUDI KASUS DI SD NEGERI 08 KOTO BALINGKA - Ismira; Nur Washli; Anggia Ekasari; Anja Kesuma Putri; Nanang Ady Saputra; Mardona Putra; Hosman Hosman (STKIP Subang, 2025)
This study aims to explore the role of hard skills in enhancing the teaching quality of educators at SD Negeri 08 Koto Balingka, West Pasaman District. A qualitative approach was employed to examine educators' perspectives and experiences in developing technical skills relevant to their teaching duties. Data were collected through in-depth interviews, direct observation, and document analysis. The findings indicate that mastery of hard skills, such as subject knowledge, the use of educational technology, and competency-based assessment skills, plays a crucial role in improving teaching effectiveness. However, the main challenges faced by educators include limited access to technology and inadequate training. Therefore, the development of hard skills through continuous training programs and enhanced access to technology is essential for improving education quality. This study suggests that educational institutions and the government support the systematic and equitable development of educators' hard skills.